Retinal Detachment Risk Among Athletes: Incidence, Predisposing Factors and Preventive Strategies - Jurczyk-Florkiewicz, Wiktoria; Bajor, Gabriela; Gniadek, Zofia; Pszczółka, Agata; Kozak, Joanna; Melka, Kacper; Szulewski, Mikołaj; Salagierska, Aleksandra; Machno, Patrycja; Matuszczak, Patryk (Quality in Sport, 2026)
Background: Retinal detachment is a severe emergency that can lead to permanent vision loss and other complications if not promptly treated. Among athletes, the risk of retinal detachment is caused by a combination of mechanical trauma, ocular health problems and factors specific to a sport. Aim: The aim of this review is to examine the incidence of retinal detachment within athletes, describe high incidence sports, identify predisposing factors, and discuss how to be safely involved in various athletic activities. Evidence suggests that collision sports may increase the likelihood of retinal injury due to blunt ocular trauma and increase the risk of peripheral retinal lesions in elite athletes. Material and methods: A structured literature search of PubMed and Google Scholar (2000-2025) was conducted using terms related to retinal detachment in athletes, sports-related eye injuries, protective eyewear, risk and predisposition factors, ocular trauma. English-language publications were analyzed. Results: Evidence indicates that high-risk sports increase the likelihood of retinal injury and retinal detachment. The significance of using the proper eye protection is crucial. Ninety per cent of all sport-related ocular injuries are likely to be preventable with proper eye protection. What is more, the collaboration between sports medicine professionals and ophthalmologists is pivotal to educate and guide sports athletes. Conclusions: Understanding the risk factors is a core for the development of preventive strategies,​​ the need for regular ophthalmic visits in athletes’ population, protective eyewear recommendations, and dedicated guidelines for athletes with enhanced risk. In spite of preserving long-term visual health in athletes there is a need for a balance between the benefits of sports participation and fathoming their hobby while broadening their knowledge and taking care of their health.